Cultura associada de feijão e milho: II - Efeitos de populações de plantas no sistema de plantio simultâneo de ambas as culturas - Aidar, Homero; Vieira, Clibas; Maffia de Oliveira, Laede; Vieira, Manoel (Revista Ceres, 2025)
An experiment was carried out at Paula Cândido, Minas Gerais, Brazil, in order to compare the effects of the combination of three maize plant populations (20, 40, and 60 thousand/ha) with five bean (Phaseolus vulgaris L.) densities (0, 40, 80, 120, and 160 thousand seeds/ha). Both crops were planted simultaneously in the same rows at the beginning of the rainy season.